Da estética à política : a contribuição de José de Guilherme Merquior para o pensamento social - Vasconcelos Filho, Marcos Antonio Rodrigues (2018)
This thesis aims to identify and present, from the reading and analysis of the bibliographical production of the Brazilian diplomat José Guilherme Merquior (1941- 1991), the main interlocutors with whom he dialogues to give shape and criticality to his thought, in order to accentuate, amid a writing marked by interdisciplinarity, the existence, among other possibilities, of a sociological approach. Among such interlocutors would be Erich Auerbach (1892-1957), Antonio Candido (1918-2017), Walter Benjamin (1892-1940), Claude Lévi-Strauss (1908-2009), Jean-Jacques Rousseau (1712-1778), Max Weber (1864-1920), Raymond Aron (1905-1983), Sir Ralf Dahrendorf (1929-2009) and Norberto Bobbio (1909-2004). Merquior is among the Brazilian thinkers whose contributions intended to establish an understanding, if not of Brazil per se, of modern society matters. In his work, such matters can be listed in at least three axes: the social basis of aesthetics, the critique of scientific paradigms, such as Marxism, structuralism and poststructuralism, and concern with the ethical and political dimension of ideas and human nature.